Evaluasi Kondisi Fisik dan Fasilitas Jembatan Penyeberangan Orang (JPO) di Jalan Jenderal Basuki Rachmat, Kota Surabaya - Irvandi Mikael Kii; Pamela Dinar Rahma; Blima Oktaviastuti (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
This study aims to conduct an in-depth analysis of the physical characteristics of the pedestrian overpass on Basuki Rachmat Street in Surabaya, as well as to assess its compliance with applicable national technical standards for pedestrian facilities. This study employs a descriptive quantitative approach through direct field observations of various physical elements of the pedestrian overpass on Basuki Rachmat Street in Surabaya. The aspects observed include stairs, walkways, safety railings, roofs, lighting systems, and accessibility. The results of the study indicate that most of the physical components of the pedestrian overpass on Basuki Rachmat Street in Surabaya meet technical requirements, particularly regarding the width of the stairs, walkways, and strong, stable safety railings. The roof structure is also in good condition as it effectively protects users from rain and heat. However, several discrepancies were identified, such as stair inclines exceeding comfort limits, uneven lighting across the entire bridge area, and limited accessibility for people with disabilities. These conditions have the potential to reduce user comfort and safety. Overall, the physical characteristics of the pedestrian overpass on Basuki Rachmat Street in Surabaya can be categorized as being in good condition and suitable for use; however, improvements are needed regarding stair slope, lighting, and accessibility to better meet the design principles for safe, comfortable, and inclusive pedestrian facilities.